Escaping jurassic government : how to recover America's lost commitment to competence - Kettl, Donald F. (Brookings Institution Press, 2016)
"The Progressive government movement reined in corporate trusts and improved the lives of sweatshop workers. It created modern government, from the Federal Reserve to the nation's budgetary and civil service policies. Ask any American today and they will tell you how our government has hit a wall with profound implications. Trust in government is low, and the success of its programs. Instead of a focus on governmental effectiveness, the movement became known for governmental size. Both political parties contributed to the decline of the Progressive ideal, helping feed the gridlock and create a government that does not work the way citizens deserve. Donald Kettl argues for a rebirth of the Progressive spirit with a dedication to making the government work better. He outlines the problems in today's government, including political pressures, proxy tools, and capacity for management. Government Reclaimed details the strategies, evidence and people necessary to strengthen governmental effectiveness and shut down the gridlock"--